Cryo‐EM structure of the human NKCC1 transporter reveals mechanisms of ion coupling and specificity. (14th October 2022) - Neumann, Caroline; Rosenbæk, Lena Lindtoft; Flygaard, Rasmus Kock; Habeck, Michael; Karlsen, Jesper Lykkegaard; Wang, Yong; Lindorff‐Larsen, Kresten; Gad, Hans Henrik; Hartmann, Rune; Lyons, Joseph Anthony; Fenton, Robert A; Nissen, Poul
Abstract: The sodium–potassium–chloride transporter NKCC1 of the SLC12 family performs Na + ‐dependent Cl − ‐ and K + ‐ion uptake across plasma membranes. NKCC1 is important for regulating cell volume, hearing, blood pressure, and regulation of hyperpolarizing GABAergic and glycinergic signaling in the central nervous system. Here, we present a 2.6 Å resolution cryo‐electron microscopy structure of human NKCC1 in the substrate‐loaded (Na +, K +, and 2 Cl − ) and occluded, inward‐facing state that has also been observed for the SLC6‐type transporters MhsT and LeuT. Cl − binding at the Cl1 site together with the nearby K + ion provides a crucial bridge between the LeuT‐fold scaffold and bundle domains. Cl − ‐ion binding at the Cl2 site seems to undertake a structural role similar to conserved glutamate of SLC6 transporters and may allow for Cl − ‐sensitive regulation of transport. Supported by functional studies in mammalian cells and computational simulations, we describe a putative Na + release pathway along transmembrane helix 5 coupled to the Cl2 site. The results provide insight into the structure–function relationship of NKCC1 with broader implications for other SLC12 family members. Synopsis: The Na + ‐K + ‐2Cl − cotransporter NKCC1 (SLC12A2) performs Na + ‐dependent uptake of Cl − and K + ions and is an important factor in ion homeostasis and osmotic control. Its mechanisms of ion recognition and release are addressed here by cryo‐EM microscopy, ion uptake studies, and molecular dynamics simulations. A 2.6 Å resolution cryo‐EM map reveals lipid molecules at a dimeric interface and three cholesterol molecules per protomer that regulate its transport activity. Analysis of the revealed intracellular water networks and bound ions indicates that the Cl – ion at a Cl2 site is released reversibly prior to Na + release. Intracellular Na + ion release is modeled and indicates guidance along transmembrane helix 5 by two negatively charged glutamate residues. The Cl2 site, which overlaps with a conserved glutamate residue in the SLC6 transporter, may sense chloride to regulate transport. Abstract : Structural and functional studies of the cation chloride cotransporter NKCC1 propose novel mechanisms for substrate release and cytoplasmic chloride sensing.